Rich client programming : plugging into the NetBeans platform - Boudreau, Tim (Prentice Hall, 2007)
The open-source NetBeans Platform is an extraordinarily powerful framework for building "write once, run anywhere" rich client applications. Now, for the first time since the release of NetBeans IDE 5.0, there's a comprehensive guide to rich client development on the NetBeans Platform. Written for Java developers and architects who have discovered that basic Swing components are not enough for them, this book will help you get started with NetBeans module development, master NetBeans' key APIs, and learn proven techniques for building reliable desktop software. Each chapter is filled with practical, step-by-step instructions for creating complete rich client applications on top of the NetBeans Platform and plugins for NetBeans IDE. Rich Client Programming 's wide-ranging content covers Why modular development makes sense for small, medium, and large applications Using NetBeans to accelerate development and improve efficiency Leveraging NetBeans productivity features, from the Component Palette to Code Completion Leveraging NetBeans' modular architecture in your own applications Implementing loosely coupled communication to improve code maintainability and robustness Managing user- and system-configuration data Building reloadable components with solid threading models Constructing sophisticated multiwindow applications and presenting rich data structures to users Adding user-configurable options Integrating Web services with NetBeans desktop applications Automating module updates and providing user help Foreword by Jonathan Schwartz Foreword by Jan Chalupa Preface About the Authors and Contributors Acknowledgments Chapter 1: Getting Started with the NetBeans Platform Chapter 2: The Benefits of Modular Programming Chapter 3: Modular Architecture Chapter 4: Loosely Coupled Communication Chapter 5: Lookup Chapter 6: Filesystems Chapter 7: Threading, Listener Patterns, and MIME Lookup Chapter 8: The Window System Chapter 9: Nodes, Explorer Views, Actions, and Presenters Chapter 10: DataObjects and DataLoaders Chapter 11: Graphical User Interfaces Chapter 12: Multiview Editors Chapter 13: Syntax Highlighting Chapter 14: Code Completion Chapter 15: Component Palettes Chapter 16: Hyperlinks Chapter 17: Annotations Chapter 18: Options Windows Chapter 19: Web Frameworks Chapter 20: Web Services Chapter 21: JavaHelp Documentation Chapter 22 Update Centers Chapter 23: Use Case 1: NetBeans Module Development Chapter 24: Use Case 2: Rich Unger on Applicat ...